Control of ambient pH on growth and stable isotopes in phytoplanktonic calcifying algae. (22nd August 2015) - Hermoso, Michaël
Abstract: The present work examines the relationship between pH‐induced changes in growth and stable isotopic composition of coccolith calcite in two coccolithophore species with a geological perspective. These species ( Gephyrocapsa oceanica and Coccolithus pelagicus ) with differing physiologies and vital effects possess a growth optimum corresponding to average pH of surface seawater in the geological period during their first known occurrence. The "ancestral" C. pelagicus has much wider pH tolerance in terms of growth rates than the more recently evolved G. oceanica . Diminished growth rates are explained by the challenge of proton translocation into the extracellular environment at low pH and enhanced aqueous CO2 limitation at high pH. Reducing the cell dynamics in this way leads to a lower degree of oxygen isotopic disequilibrium in G. oceanica . In contrast, the slower growing species C. pelagicus, which typically precipitates near‐equilibrium calcite, does not show any modulation of oxygen isotope signals with changing pH. Overall, carbon and oxygen isotope compositions are best explained by the degree of utilization of the internal dissolved inorganic carbon (DIC) pool and the dynamics of isotopic reequilibration inside the cell. Thus, the "carbonate ion effect" may not apply to coccolithophores. This difference with foraminifera can be traced to different modes of DIC incorporation into these two distinct biomineralizing organisms. From a geological perspective, these findings have implications for refining the use of oxygen isotopes to infer more reliable sea surface temperatures (SSTs) from fossil carbonates and contribute to a better understanding of how climate‐relevant parameters are recorded in the sedimentary archive. Key Points: Contrasting changes in oxygen isotopes with pH between coccolith species No carbonate ion effect operating in coccolithophores as in foraminifera C. pelagicus can be used for Neogene SST reconstruction without bias due to pH